2013
DOI: 10.1097/sla.0b013e31826f4b0e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Preoperative Biliary Drainage in Jaundiced Patients Who Are Candidates for Pancreatoduodenectomy or Hepatic Resection

Abstract: : A multidisciplinary evaluation (made by a surgeon, biliary endoscopist, gastroenterologist, and radiologist) of jaundiced neoplastic patients should be performed before deciding to perform biliary drainage. Middle-distal obstruction in patients who are candidates for PD does not usually require routine biliary drainage. Proximal obstruction in patients who are candidates for major hepatic resection in the majority of cases requires a drain; however, the type, site, number, and approach must be defined and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
125
2
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 83 publications
1
125
2
4
Order By: Relevance
“…[5][6][7][8] However, in Japan, preoperative biliary drainage is generally carried out. This is attributed to the fact that appropriately conducted preoperative biliary drainage can decrease the risk of postoperative complications 22 and that surgical waiting time, including detailed preoperative examinations, is usually several weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] However, in Japan, preoperative biliary drainage is generally carried out. This is attributed to the fact that appropriately conducted preoperative biliary drainage can decrease the risk of postoperative complications 22 and that surgical waiting time, including detailed preoperative examinations, is usually several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The development of preoperative cholangitis after preoperative drainage has been reported to increase the incidence of postoperative complications, particularly pancreatic fistula. 9 Pancreatic fistula is a risk factor for surgical site infection.…”
mentioning
confidence: 99%
“…Major drawbacks for ENBD are patient's discomfort and high risk of displacement of the tube. Moreover, the reduction in serum bilirubin is reportedly lower than the other procedures and a longer preoperative hospital stay may be required; also, contemporary drainage of both liver lobes is not achievable with only one tube [20]. Interestingly, Yoshida et al suggested that per-os reintroduction of drained bile may improve immune and hepatic function and overall general status, supporting the hypothesis that bile replacement may be beneficial for patients undergoing major hepatectomy [21].…”
Section: Drainage Techniquesmentioning
confidence: 84%
“…In the event of severe complications related to obstructive jaundice, the majority of authors recommend urgent treatment of hyperbilirubinemia, regardless of the origin of the disease; conversely, isolated finding of elevated serum bilirubin may not be per se an indication to perform PBD particularly in the case of malignancies involving the distal portion of common bile duct [20,37,38]. However, as far as HC is concerned, poor evidence is available and data appear discordant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation